Intraarticular injection autologous platelet‐rich plasma and bone marrow concentrate in a goat osteoarthritis model. Issue 8 (30th March 2018) - Wang, Zhen; Zhai, Chenjun; Fei, Hao; Hu, Junzheng; Cui, Weiding; Wang, Zhen; Li, Zeng; Fan, Weimin
ABSTRACT: To evaluate the effects of intraarticular injections of autologous platelet‐rich plasma (PRP) or bone marrow concentrate (BMC) on osteoarthritis (OA), 24 adult goats were equally divided into control (Ctrl), saline (NS), PRP, and BMC groups, and OA was induced by surgery in NS, PRP, and BMC groups. Autologous PRP and BMC were obtained from whole blood and bone marrow aspirates, respectively. The data revealed, platelets were increased in BMC by 1.8‐fold, monocytes by 5.6‐fold, TGF‐β1 by 7.7‐fold, and IGF‐1 by 3.6‐fold ( p  < 0.05), and platelets were increased in PRP by 2.9‐fold, and TGF‐β1 by 3.3‐fold ( p  < 0.05). From the sixth week post‐operation, saline, PRP, and BMC were administered by intraarticular injection once every 4 weeks, three consecutive times. After the animals were sacrificed, inflammatory cytokines in the synovial fluid was measured, and bone and cartilage degeneration progression was observed by macroscopy, histology, and immunohistochemistry. Compared with the NS group, the level of inflammatory cytokines was reduced in the PRP and BMC groups ( p  < 0.05). Histologically, delayed cartilage degeneration and higher levels of extracellular matrix (ECM) were observed in both PRP and BMC treated groups ( p  < 0.05). Furthermore, the BMC group showed greater cartilage protection and less ECM loss than the PRP group ( p  < 0.05). In summary, this study showed that intraarticular injection of autologous PRP and BMC has therapeutic efficacy in a goat osteoarthritis model, with the greater benefit in terms of cartilage protection being observed in the BMC‐treated group than PRP. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:2140–2146, 2018.